Prediction Score for persisting perfusion defects after pulmonary embolism - Mrozek, Jan; Necasova, Tereza; Svoboda, Michal; Simkova, Iveta; Jansa, Pavel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2020)
AIMS: Long-term persistence of perfusion defect after pulmonaryembolism (PE) may lead to the development of chronic thromboembolic pulmonary hypertension. Identification of patients at risk of such a complication using a scoring system would be beneficial in clinical practice. Here, we aimed to derive a score for predicting persistence of perfusion defects after PE. METHODS: 83 patients after PE were re-examined 6, 12 and 24 months after the PE episode. Data collected at the time of PE and perfusion status during follow-ups were used for modelling perfusion defects persistence using the Cox proportional hazards model and validated using bootstrap method. RESULTS: A simple scoring system utilizing two variables (hemoglobin levels and age at the time of PE) was developed. Patients with hemoglobin levels over 140 g/L who were older than 65 years were at the highest risk of perfusion defects; in patients with the same hemoglobin levels and age <65 years, the risk was reduced by 79%, and by 89% in patients with hemoglobin <140 g/L. CONCLUSION: The proposed scoring system may be useful in clinical practice for identifying patients with high risk of persisting perfusion defects, flagging them for closer follow up, thus improving the effectiveness of long-term treatment of patients after PE.
Keywords: prediction score; proporcionální rizikové modely; Humans; pravidla klinického rozhodování; lidé středního věku; Proportional Hazards Models; echokardiografie; Echocardiography; perfusion defects; Female; rizikové faktory; Aged; dospělí; Hemoglobins; věkové faktory; senioři; lidé; plicní embolie; Hypertension, Pulmonary; reperfusion; Pulmonary Embolism; risk score; classification; Adult; plicní hypertenze; ženské pohlaví; Male; Middle Aged; Aged, 80 and over; pulmonary embolism; senioři nad 80 let; Age Factors; mužské pohlaví; antikoagulancia; hemoglobiny; Anticoagulants; Clinical Decision Rules; Risk Factors